Clinical and subclinical bovine mastitis in area of Kilkis - ILIADIS (Ν. ΗΛΙΑΔΗΣ), N.; PETRIDOU (Ε.N.ΠΕΤΡΙΔΟΥ), E. N.; FOUKOS (Α. ΦΟΥΚΟΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study 216 milk samples from equal number of quarters were examined. The results from microbiological examination and the performed California test revealed that 82 samples (38%) were collected from quartres with subclinical mastitis. Coagulase-negative staphylococci were the most frequent pathogens isolated from the examined milk samples, representing 47.5% of the total isolated strains. Sensitivity test of the strains to certain antimicrobials showed higher performance of gentamycine (90.9% of the cases). On a descending sequence cephalotin (75%), oxalinique acid (63.6%) and ampicilline (54.2%) were the antimicrobials to which sensitivity of the strains was higher than 50%. On the contrary, tetracycline, tincomycine, erythromycine and penicilline G performance was lower than 50%.